Cigarette Filter-Based Membranes with Tannin and FeCl₃ Additives for Enhancing the Antifouling Properties of Oil Emulsion Filtration - Anisa Luthfiana; Sri Mulyati; Nasrul Arahman; Aulia Cintia Ambarita; Muhammad Prayogie Aulia (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Industries in Indonesia significantly contribute to the economy by increasing foreign exchange earnings and creating job opportunities. However, industrial activities also negatively impact the environment, particularly water pollution caused by liquid waste containing oil emulsions. This research aims to develop a membrane based on cigarette filters as an alternative to cellulose acetate for separating oil emulsions in water. Cigarette filters were processed into membranes with tannic acid (TA) and ferric chloride (FeCl3) as additives using a vacuum-filtration coating technique. The resulting membranes were tested for their characteristics and performance, including morphological analysis, functional group analysis, hydrophilicity, water uptake, porosity, pure water flux, selectivity toward oil emulsions (artificial emulsions from CPO and sodium dodecyl sulfate (SDS)) and antifouling properties. The results showed that membranes with additives exhibited more uniform pores, asymmetric structures, and improved surface characteristics. The addition of tannic acid 2.4 mmol and FeCl3 3.7 mmol also enhanced the antifouling properties of the membranes, although it decreased the pure water flux. Membranes without additives (M1) and with additives (M2) were compared for pure water flux, separation efficiency, and antifouling properties. M2 exhibited a lower flux (15.03 L/m2·h) than M1 (19.69 L/m2·h) due to reduced porosity. Although the oil emulsion selectivity of M2 (97.80%) showed no significant improvement compared to M1 (97.79%), the addition of additives notably enhanced the antifouling performance. M2 demonstrated a flux recovery ratio (FRR) of 71.22%, significantly higher than M1’s FRR of 46.01%, indicating the effectiveness of the additives in reducing fouling and improving membrane reusability. The membranes achieved high selectivity for oil emulsions with a separation efficiency of up to 97%. These findings suggest that using cigarette filters as the base material for membranes and adding additives can provide an efficient and environmentally friendly solution to reducing oil emulsion pollution.